Giving Form to Consciousness - Dempsey, Jessica (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
Engaging Debbie Hopkin’s arguments on fly less or no fly movements, this essay reflects on faculty efforts to reduce aviation-related emissions at the University of British Columbia.